2017
DOI: 10.4038/jas.v12i3.8262
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Analysis and Fruit Quality of Two Varieties of Tomato under Hand Weeding and Pendimethalin Herbicide

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This could be attributed to lack of satisfactory weed control, most importantly where one hand weeding at 3WAP. Similar observations have been reported by Olayinka et al (2017) in their studies of weed control in tomato. The most preponderant families were Poaceae Fabaceae and Asteraceae.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This could be attributed to lack of satisfactory weed control, most importantly where one hand weeding at 3WAP. Similar observations have been reported by Olayinka et al (2017) in their studies of weed control in tomato. The most preponderant families were Poaceae Fabaceae and Asteraceae.…”
Section: Resultssupporting
confidence: 91%
“…Varietal difference showed that yield and yield attributes were higher in Ife brown than Tvx 3236. This could be attributed to differential genetic makeup of the crops (Hernandez et al, 2008;Olayinka and Etejere, 2015;Olayinka et al, 2017). .001 N. B: Means in the same column having the same superscripts are not significantly different at (P<0.05).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are a number of reports on influence of herbicides on yield parameters and crop yield. In this regard, the grain yield of cowpea genotypes showed a substantial level of disparity due to differential genetic makeup of the crops or influence of the location since yield is quantitatively hereditary [48,38] and [35]. However, [49] likewise found that genetic effects and ecological factors affected agronomic performance of cowpea genotypes.…”
Section: Discussionmentioning
confidence: 99%